ETHNOMEDICINAL POTENTIAL OF SARCOSTEMMA ACIDUM IN DIFFERENT REGIONS IN INDIA - Pandey, Sandeep (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study is to collect and enumerate the uses of Sarcostemma acidum (Somlata) in the treatments of various diseases and to evaluate knowledgeable information on traditional practitioners among different communities in India. Methods: This was an extensive survey of literature on ethnopharmacological uses of S. acidum in Indian system of traditional medicine (TM), and the collected information documented in tabular form. Results: The collected literature reveals that the plant is used as TM by the indigenous community in states such as Madhya Pradesh, Gujarat, Telangana, Karnataka, Andhra Pradesh, Tamil Nadu, Rajasthan, Maharashtra, Uttaranchal, West Bengal, Uttar Pradesh, and Andaman and Nicobar Islands. These communities are using the whole plant in 29%, stem 15%, latex 24%, roots 10%, leaves 17%, and flowers in 5% of cases for treating 40 different types of ailments important being ear ache, snake bite, rheumatism, dog bite, emetic, chronic ulcer, and bone fracture. Conclusions: Due to insufficient knowledge, lack of information and overexploitation has made the plant species under threat. The present survey provides proper documentation of ethnomedicinal uses of the plant and provides a valuable source of information for traditional practitioners and researchers with a special emphasis on developing policies for conservation and sustainable use of this species.